2008
DOI: 10.1111/j.1365-2435.2008.01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Even after death the endophytic fungus of Schedonorus phoenix reduces the arbuscular mycorrhizas of other plants

Abstract: Summary 1.Plants can host microbial communities whose integrated functions are often responsible for their success. Understanding mechanisms regulating such functions is thus a major goal in ecology. 2. Fungal endophytes of grasses, particularly of the genus Neotyphodium , have been reported to reduce colonization of their host plant by arbuscular mycorrhizal (AM) fungi. However, it is unclear which mechanism(s) may explain the effects produced by the endophyte and whether these effects are present in nature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
68
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 52 publications
(67 reference statements)
3
68
2
1
Order By: Relevance
“…Nevertheless, other mechanisms, such as leaching and decomposition, are not discarded and probably may be occurring simultaneously. In this sense, Antunes et al (2008) have proposed that endophyte chemical compounds are leached into the soil after the death of the plant host.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, other mechanisms, such as leaching and decomposition, are not discarded and probably may be occurring simultaneously. In this sense, Antunes et al (2008) have proposed that endophyte chemical compounds are leached into the soil after the death of the plant host.…”
Section: Discussionmentioning
confidence: 99%
“…According to Antunes et al (2008) there are at least three ecologically relevant mechanisms by which endophyte compounds are released into the soil and might influence AM fungi. One mechanism could be through both the guttation fluid and 'cut leaf fluid' of endophyte infected plants (Koulman et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endophyte negative effects on soil biota activity have been generally associated to the aboveground litter inputs of the host plants (Antunes et al 2008;Lemons et al 2005;Omacini et al 2004). Instead, this study demonstrates that 7 months, one growing season for an annual host, was enough to detect significant changes in the soil functional capacity (by using catabolic response profiles) and perceptible differences in the activity of soil fungi (by using selective inhibition with antibiotics) as well as in the structure of bacterial communities in relation to Table 1 Mean values for soil parameters and above and below ground biomass of Lolium multiflorum infected or uninfected with Neotyphodium occultans (+E and −E, respectively) at the end of the growing season (n=12) endophyte infection level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, endophyte presence can modify litter decomposition by changing the quality of the litter produced by infected plants and by altering micro-environmental conditions (Lemons et al 2005;Omacini et al 2004). Moreover, previous studies indicated that the endophyte may reduce colonization by arbuscular mycorrhizal fungi either in the host plant (Mack and Rudgers 2008;Omacini et al 2006) or in the plants growing in next generation after the death of host plants (Antunes et al 2008).…”
mentioning
confidence: 99%